Biodistribution of Mesenchymal Stem/Stromal Cells in a Preclinical Setting - Luc Sensebé; Sandrine Fleury-Cappellesso (Hindawi Limited, 2013)
Due to their multi/pluripotency and immunosuppressive properties, mesenchymal stem/stromal cells (MSCs) are important tools for treatment of immune disorders and tissue repair. The increasing uses of MSCs lead to the development of production processes that need to be in accordance with good manufacturing practices (GMP). In Europe, MSCs are somatic cell-therapy products, referred to as advanced-therapy medicinal products (ATMPs), and in the United States MSCs must comply with current good tissue practice requirements. The safety and efficacy of MSCs must be ensured, whatever the cell source, and studies of dose and biodistribution are important aspects of safety testing. Preclinical data on biodistribution and pharmacodynamics are mandatory for approval. It is important to demonstrate that MSCs do not have unwanted homing that could drive to inappropriate differentiation in some organ or to support cancer development as suggested in some experiments. All these aspects should be addressed in a risk-based approach according to recently published guidelines by EMA. In the present article, we summarize the main approaches for labeling and tracking of infused MSCs, report on current animal models, and give an overview of available results on biodistribution.